(untitled) (Biological Sciences - PJSIR, 2002)
Soil impedance measuring meter is relatively a new device and utilises the principle of measuring the dielectric constant of the soil, and hence water content by soil electrical impedance method at 100 MHz. The probe is supplied with a general calibration by the manufacturer and very little has been published on the materials-specific calibration. Hence, the output (mV) of the probe was calibrated versus volumetric water content (8) of silty clay loam soils, loamy very fine sand soil and chalky material. For 8v <0.6 m 3m-3, a third order polynomial relationship between 8v and the probe ’s output was found suitable (r2=0.99) for calibration . A good correlation was found between moisture content measured by this new probe and that with neutron probe under field condition, for silty clay loam soil (r=0.96) and for chalky material (r=0.97). The probe is comparatively small and easy to install but its effective sampling volume is limited (42.4 cm2). Therefore, it is most suitable for homogeneous soils and pot experiments. The sensitivity of the probe is greatly influenced by conditions close to the central rod and a 0.5 mm annular gap between this rod and the surrounding material resulted in 42% reduction in output.